HABITUATION OF TITLE LITERATION IN EMPOWERING READING INTEREST IN STUDENTS OF STATE 01 PANDEAN MADIUN - Nur Samsiyah; Edi Suryo (Universitas Negeri Medan, 2019)
Abstract: This study aims to describe the implementation of habituation of fairy tale literacy activities in empowering reading interest in sisawa, the location of this study in SDN 01 Pandean, Taman Kota Madiun District. The method used in this research is a qualitative approach. Data sources used in this study are primary data sources and secondary data sources. Data collection techniques by interview, observation, and documentation / archives. While validation is used to test the truth of data using source triangulation, and technique triangulation. The results showed that the habituation of fairy tale literacy activities called DOPARI (Fairytale Morning) can empower students' interest in reading especially IVC class SDN 01 Pandean. Empowerment of interest in reading is done is giving all students the opportunity to follow the activities of DOPARI in listening to a fairy tale , became a storyteller, giving a fairy tale about the question and answer session which was read and member i chance students to answer questions, summarizing the content of reading as well as giving gifts or rewards. There are facilities in the form of reading books in each class and in the library. Keywords: habituation, literacy, interest in reading